Focused and inclusive actions could ensure the persistence of East Africa's last known viable dugong subpopulation. Issue 7 (4th May 2022) - Trotzuk, Evan; Findlay, Ken; Taju, Alima; Cockcroft, Vic; Guissamulo, Almeida; Araman, Armindo; Matos, Lorena; Gaylard, Angela
Abstract: Although the dugongs of Mozambique's Bazaruto Archipelago are the last known viable subpopulation along the East African coast, they remain threatened by a variety of anthropogenic and natural pressures that must be addressed to ensure their persistence. We aimed to establish recent trends in dugong abundance through a series of aerial surveys carried out between 2017 and 2021 over the Bazaruto seascape. We also assessed hotspots of dugong distribution in this region where targeted conservation measures may prove most effective. Finally, we modeled dugong population growth and mortality rates under varying scenarios to better understand the level of risk to anthropogenic mortality. We derived a total abundance of 325 SD 145 dugongs. While the estimates from this study and those from surveys in 2006–2007 (359 SD 137) suggest that dugong abundance has not changed significantly over the past 15 years, the confidence intervals of these estimates are too wide to detect potentially small changes relative to the subpopulation's size. The distribution of dugong sightings within the Bazaruto seascape over the 5‐year period indicates two core zones, one of which occurs outside the limits of established conservation areas. Population viability analyses demonstrated variability around rates of unnatural mortality that would cause long‐term decline in abundance. Together, these results provide strong motivations for higher level conservation actions such as the expansion and management of formal marine protected areas in the region and the listing of the East African dugong subpopulation within the IUCN Red List of Threatened Species. Our study also highlights the importance of developing alternative livelihoods and sustainably managing small‐scale fisheries in collaboration with local communities and other stakeholders in order to reduce the prevalence of fishing equipment and anthropogenic activities that directly or indirectly threaten dugongs in the Bazaruto seascape.